Pre-harvest Sprouting and Grain Dormancy in Sorghum bicolor: What Have We Learned? - Benech-Arnold, Roberto L.; Rodríguez, María V. (Frontiers in Plant Science, 2018)
The possibility of obtaining sorghum grains with quality to match the standards for a diversity of end-uses is frequently hampered by the susceptibility to pre-harvest sprouting (PHS) displayed by many elite genotypes. For these reasons, obtaining resistance to PHS is considered in sorghum breeding programs, particularly when the crop is expected to approach harvest maturity under rainy or damp conditions prevalence. As in other cereals, the primary cause for sprouting susceptibility is a low dormancy prior to crop harvest; in consequence, our research group has focused in understanding the mechanisms through which the duration of dormancy is differentially controlled in genotypes with contrasting sprouting behavior. With this aim we have been using two inbred, red-grained but tannin-less lines, as a model system: IS9530 (sprouting resistant) and Redland B2 (sprouting susceptible). Redland B2 grains are able to germinate well before reaching physiological maturity while IS9530 ones can start to germinate at 40-45 DAP, well after physiological maturity. Our results show that the anticipated dormancy loss displayed by Redland B2 grains is related to a reduced embryo sensitivity to ABA and increased levels of GA upon imbibition. In turn, transcriptional data showed that ABA signal transduction is impaired in Redland B2, which appears to have an impact on GA catabolism, thus affecting the overall GA/ABA balance that regulates germination. QTL analyses were conducted to test whether previous candidate genes were located in a dormancy QTL, but also to identify new genes involved in dormancy. These analyses yielded several dormancy QTL and one of them located in chromosome 9 (qGI-9), was consistently detected even across environments. Fine mapping is already in progress to narrow down the number of candidate genes in qGI-9.